Studying The Effectiveness Of An Intelligent Vehicle Tracking System In Reducing Ambulance Arrival Time (The Review of Diabetic Studies, 2025)
This study aims to analyze the effectiveness of an intelligent vehicle tracking system in reducing the time it takes ambulances to reach accident and emergency sites, and its role in improving response efficiency and the speed of providing emergency services. Response time is one of the most important indicators of the quality of emergency services, as any delay in arrival can lead to worsening injuries or higher mortality rates. Therefore, health institutions and concerned authorities, such as the Saudi Red Crescent Authority, seek to employ modern technologies to enhance the speed of response and the accuracy of field monitoring. The study relied on the descriptive analytical approach, and a questionnaire was used and distributed to a sample of (200) participants from ambulance drivers, field supervisors, and emergency technicians. The data were analyzed using appropriate statistical methods to test the study hypotheses. The results showed that the implementation of the smart vehicle tracking system significantly reduced arrival time, improved location accuracy, and enhanced immediate communication between the operations room and field vehicles. The results also showed that the system supports rapid decision-making in allocating ambulances according to emergency priorities. The study recommended the widespread use of smart tracking systems across all regions of the Kingdom, the development of ongoing training programs for employees on how to use these systems efficiently, and linking them to traffic and road systems to increase their technical effectiveness in saving lives and improving the quality of emergency services.